41.3k views
5 votes
Solve the equation and show all work please show steps!!
2n-3=9

2 Answers

5 votes
2n-3=9
------------
Add 3 to each side
2n−3+3=9+3
2n = 12
------------------
Divide each side by 2
2n ÷ 2 = 12 ÷ 2
n = 6

User Mitch VanDuyn
by
6.0k points
3 votes
2n - 3 = 9

If you are solving for n:

Isolate it by doing the opposite of PEMDAS; Also, what you do to one side you do to the other (because of the equal sign)


2n - 3 = 9

2n - 3 (+3) = 9 (+3)

2n = 12

2n/2 = 12/2

n = 6

n = 6 is your answer

hope this helps
User Danielcorreia
by
5.3k points